2003
DOI: 10.1046/j.1365-2699.2003.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Australian biogeographical connections and the phylogeny of large genera in the plant family Myrtaceae

Abstract: Aim To compare the phylogeny of the eucalypt and melaleuca groups with geological events and ages of fossils to discover the time frame of clade divergences. Location Australia, New Caledonia, New Guinea, Indonesian Archipelago. Methods We compare published molecular phylogenies of the eucalypt and melaleuca groups of the plant family Myrtaceae with geological history and known fossil records from the Cretaceous and Cenozoic. Results The Australasian eucalypt group includes seven genera, of which some are reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
173
2
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(191 citation statements)
references
References 43 publications
10
173
2
6
Order By: Relevance
“…The outgroup taxa formed a clade at the base of the tree, with the relationship (Stockwellia, Eucalyptopsis + Allosyncarpia). On flower development, the clade of these three rainforest genera had the relationship: Allosyncarpia, (Stockwellia + Eucalyptopsis) (Carr et al, 2002;Ladiges et al, 2003), which was also supported by Parra-O et al (2006) based on a combined data set of nrETS and ITS. The monophyly of Corymbia has previously been proposed based on morphological and anatomical characters (Hill and Johnson, 1995;Ladiges et al, 1995), and recently, by DNA data from the ETS (Parra-O et al, 2006).…”
Section: Eucalypt Microsatellite Phylogeny 1129mentioning
confidence: 62%
See 2 more Smart Citations
“…The outgroup taxa formed a clade at the base of the tree, with the relationship (Stockwellia, Eucalyptopsis + Allosyncarpia). On flower development, the clade of these three rainforest genera had the relationship: Allosyncarpia, (Stockwellia + Eucalyptopsis) (Carr et al, 2002;Ladiges et al, 2003), which was also supported by Parra-O et al (2006) based on a combined data set of nrETS and ITS. The monophyly of Corymbia has previously been proposed based on morphological and anatomical characters (Hill and Johnson, 1995;Ladiges et al, 1995), and recently, by DNA data from the ETS (Parra-O et al, 2006).…”
Section: Eucalypt Microsatellite Phylogeny 1129mentioning
confidence: 62%
“…This observation may indicate that Eucalyptus is a faster evolving clade, thereby accumulating more mutations in the flanking sequences of the SSRs. SSR analysis excluded Arillastrum because available morphological and molecular data (Hill and Johnson, 1995;Udovicic and Ladiges, 2000;Wilson et al, 2001;Steane et al, 2002) put this genus the farthest from Corymbia among the eucalypts; Ladiges et al (2003) suggested, based on biogeography, that the divergence of Arillastrum from the other eucalypt genera may be as old as Late Cretaceous (70 MYA; see also Crisp et al (2004). These data suggested a potentially low prospect of transferring Corymbia SSRs to Arillastrum.…”
Section: Ascertainment Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Why then have eucalypts not taken over the seasonally dry regions of the world? During the Miocene, eucalypts were present in New Zealand and Southeast Asia in association with other sclerophyll and xeric flora, such as acacias, chenopods and Casuarinaceae 7,29,30 . At this time, there was an abundance of charcoal, indicating frequent burning in these communities 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…is a pantropical family of trees and shrubs with approximately 5500 species, divided into two subfamilies, 17 tribes and 142 genera (Wilson et al 2005, Govaerts et al 2008). This family is particularly diverse in the southern hemisphere (Ladiges et al 2003), with a high diversity in Central America (McVaugh 1968), South America (Landrum 1988) and Australia (Lucas et al 2007, Thornhill & Crisp 2012. The members of this family are woody, with entire, simple, evergreen and mostly opposite leaves, with internal phloem and oil glands (Ciccarelli et al 2008, Cronquist 1981, Metcalfe & Chalk 1979.…”
Section: Introductionmentioning
confidence: 99%